Study of PSP and TTX in lagocephalus species of Sarawak waters - Syamila Fatin, binti Ismail (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Blowfish orglobefish are the othercomrron names for Puffer Fish that has been named after their habit of inflating themselves in water whenever felt threatened. In Malaysia, Lagocephalus lunaris, L. sceleratus and also L. spadiceus are the most comrnon species ofpuffer fish consumed. Pufferfish mainly from Tetraodontidae family known to possess a saxitoxin (STX) or tetrodotoxin (TTX) which can cause fish poisoning and adverse effect to human health. Lagocephalus lunaris and L. spadiceus were identified by looking at the distribution of dorsal spines. The morphological measurement was-measured by standard measuring using model PA -251 electronic beam balance and Wildco Fish measuring board. Overall, extraction samples were shown to be toxic from TTX. L. sceleratus gives the highest value of TTX from LC-MS/MS findings from muscle part (18.9 MU/g) while the skin gives weakest concentration (1.08 MU/g) of TTX. From this findings, TLC, HPLC-FLD and LC-MS/MS were used as potential tools to determine the presence ofsaxitoxin and tetrodotoxin and its concentration in Mouse Unit per gram (MU/g). This study found that, there is no positive results for saxitoxin from all samples.